2017
DOI: 10.21776/ub.jpacr.2017.006.03.355
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extract (Camellia sinensis L.) Effects on Uric Acid Levels on Hyperuricemia Rats (Rattus norvegicus)

Abstract: Uric acid is the end product of purine degradation. When uric acid levels exceed normal limits, it will build up and cause hyperuricemia. Allopurinol is one of the most effective and common medicine for hyperuricemia, but it brings serious side effects, therefore it is needed alternative therapy for hyperuricemia. One plant that may be expected to low uric acid levels is green tea (Camellia sinensis L.), that contains many antioxidants polyphenols, especially flavonoids. Flavonoid has strong antioxidant proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Furthermore, these dosages reduced the expression of URAT1 (p < 0.05), as well as increasing the expression of OAT1 and OAT3 in the kidneys (p < 0.01). Overall, the results suggested that GTP reduced UA levels by inhibiting UA production and increasing its excretion [101].…”
Section: Regulation Of the Renal Uric Acid Transportermentioning
confidence: 81%
“…Furthermore, these dosages reduced the expression of URAT1 (p < 0.05), as well as increasing the expression of OAT1 and OAT3 in the kidneys (p < 0.01). Overall, the results suggested that GTP reduced UA levels by inhibiting UA production and increasing its excretion [101].…”
Section: Regulation Of the Renal Uric Acid Transportermentioning
confidence: 81%
“…Hematological and biochemical analysis of the blood samples were taken on day 5 and results are presented in Supplementary Tables 4 and 5. All results were within the normal reference range (60)(61)(62)(63), indicating no effects of the treatments on blood parameters.…”
Section: Hematological and Biochemical Analysismentioning
confidence: 63%
“…Hematological and biochemical analyses of the blood samples were taken on day 5 and results are displayed in Tables 2, 3 , respectively. The references range value of both hematological and biochemical analyses were based on these following studies Nugraheni et al (2017) , He et al (2017) , Houtmeyers et al (2016) and Petterino and Argentino-Storino (2006) . The hematological analysis revealed a significant increase in mean corpuscular hemoglobin concentration (MCHC).…”
Section: Resultsmentioning
confidence: 99%